STUDENTS’ PERCEPTION TOWARDS WORDWALL AS AN ONLINE ASSESSMENT PLATFORM IN TEACHING ENGLISH AT MTS ALIF LAAM MIIM SURABAYA - Naufal Ilyas Saputra; Haris Dibdyaningsih; Rizki Ramadhan (Journal of English Language Teaching and Islamic Integration, 2023)
The aim of this research is to know students’ perception towards wordwall as an online assessment platform in teaching English at MTs Alif Laam Miim Surabaya. Perceptions is individuals organize and interpret process their sensory and impressions to get a conclusion about something to their society. This research was conducted at MTs Alif Laam Miim Surabaya and the subject of the research were students from IX B class. This research applied descriptive research. Technique of collecting data used in this research were share a questionnaire and do an interview. The data were analyzed in three steps; (1) collecting data, (2) data reduction, (3) display the final data. Due to the research and discussion, it can be concluded, that perception of students is trend to the positive perception, based on data showing 16 out of 25 students have a positive perception, 8 students are positive, and 1 student is trends to a negative perception. The findings in this study include; (1) Students feel happy and amazed when using Wordwall, (2) Students want to use Wordwall in the future, (3) There is a growing competitive aura among students, (4) Students feel more enthusiastic during Wordwall sessions, (5) Students find Wordwall easy used, (6) Wordwall features are attractive to students, (7) Wordwall has an attractive appearance for students.